The Dynamics of Organizational Influence on Debt Structure, Bank Loan Financing and Corporate Performance: A Comprehensive Study in China - Faye, Nicolas Diodji Mamadou; Ndao, El Hadji Omar; Tozo, Kokou W.; Gilhaimé, Mouanda; Abdul-Latif, Mohammed (New Advances in Business, Management and Economics Vol. 2, 2025)
This paper examines the incidence of firm value chain power on its exterior financing liabilities, bank loan financing and firm performance. Traditional theory is used to explain its link with upstream and downstream firms from the optics of firm working capital management. Yet, significant late investigations reveal that the framework of company working capital is deeply driven by the firm’s posture in the upstream and downstream industry chain. The data for this study has been taken from a single trustworthy data source which is the China Stock Market and Accounting Research (CSMAR). To test empirically the proposed hypotheses, this study has collected cross-sectional data from 13,653 firms from 2006 to 2016. The findings show that the volume of financing obligations is smaller in value-chain industries with greater power. The findings also indicate that firms with higher firm power tend to employ non-cost commercial credit for financing and have fewer financing liabilities. The study also shows that bank sector creditors provide more money to big businesses and that banks only acknowledge the function of firm power in stable, large-scale businesses. Additionally, firm power has no considerable impact on the maturity of bank loans. After last, this study moreover unveils the economic outcomes of the effect of firm value chain power across the differences in firm financial performance. Low-scale, great-growth firms with bigger firm power get the best financial performance. Companies with greater value chain power get access to loans with low interest rates, higher amounts, and long-term maturity. Finally, the results indicate that companies with greater value chain power tend to show good performance.